Diffuse Gonococcal Infection (DGI) in a Patient with Treatment-Refractory Acetylcholine Receptor Antibody-Positive (AChR+) Generalized Myasthenia Gravis (gMG) Treated with Eculizumab - Nakul Katyal; Latika Nirola; Naureen Narula; Raghav Govindarajan (Case Reports in Neurological Medicine)
Patients receiving complement inhibitor, eculizumab, are at high risk for infections with encapsulated organisms such as Neisseria due to impaired opsonophagocytic activity. Impaired complement immunity may increase the risk for dissemination of asymptomatic Neisseria gonorrhoeae. Disseminated Gonococcal Infection (DGI) is a rare but potentially life-threatening complication associated with eculizumab. Physicians should obtain adequate sexual histories from the patients and educate them on safe sexual practices. Here, we describe a case of DGI in a 32-year-old African American female patient with acetylcholine receptor antibody-positive (AChR+) generalized myasthenia gravis (gMG), receiving eculizumab.